Taxing the monopolistic polluter: A reconsideration - Alfred Endres (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1981)
The response of a monopolistic polluter to the imposition of an emission tax and its welfare implications are examined. The cases of output reduction as the sole means for pollution control and of additional means being feasible are considered. It turns out that in the second case the tax may increase social welfare even in the case of a firm whose market power is more distorting than its externality generation. The tax, however, is unable to achieve a predetermined target level of pollution at minimum social cost in the case of a monopolistic polluter.
Keywords: 330